HUBUNGAN PENGETAHUAN DAN KINERJA KADER TERHADAP KUNJUNGAN BAYI BALITA KE POSYANDU DI PUSKESMAS LUBUK BAJA KOTA BATAM - Siti Alfiah; Rini Susanti (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2017)
The success development in the health fields is concentrated at the attempts to reduce the mortality rate of infants and toddlers at the same time. The purpose of this research is to analyze whether there is a correlation between knowledge and performance of the health care workers to the number of the babies, specifically the ones under five years old, to visit the posyandu as an integral part of the Lubuk Baja Health Centre in Batam.This study is a descriptive analytic research with 56 respondentsthat covers all health care workers in the service area ofLubuk Baja Health Care. The data is analyzed using Chi Square statistical test at significance level of 95%. The result reveals that based on the respondentsâ€™ characteristic, it was obtained 56 respondents have good knowledge level and able to apply their knowledge to posyanduactivities. Besides, it is also noted that 44 respondents have well performance. On the other hand, the researchersdiscover 28 toddlers getgood treatment meanwhile 28 of them are not treated very well. Therefore, it can be concluded that there is no significant correlation between knowledge levels and performance of the health care workers to the number of theunder-five years children to visits the posyanduwhich indicated byÂ  each of p> 0.05 for knowledge and performance. In general, knowledge and good performance of posyandu cadres and society surroundingsaretwo very important aspects to improvethe number of the children to attend the posyandu. As the suggestion, it is expected that theposyandu cadres and society to be more concerned about the presence of posyandufor benefit of the newborns as well as the enhancement of the health sciences for life.